2021
DOI: 10.1111/pce.14191
|View full text |Cite
|
Sign up to set email alerts
|

Rice ACID PHOSPHATASE 1 regulates Pi stress adaptation by maintaining intracellular Pi homeostasis

Abstract: The concentration and homeostasis of intracellular phosphate (Pi) are crucial for sustaining cell metabolism and growth. During short‐term Pi starvation, intracellular Pi is maintained relatively constant at the expense of vacuolar Pi. After the vacuolar stored Pi is exhausted, the plant cells induce the synthesis of intracellular acid phosphatase (APase) to recycle Pi from expendable organic phosphate (Po). In this study, the expression, enzymatic activity and subcellular localization of ACID PHOSPHATASE 1 (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In response to P deficiency, plants evolved a series of intelligent adaptive mechanisms to improve P availability and increase its uptake efficiency, one of which was the production and secretion of acid phosphatase (ACP) [ 39 , 40 ]. The increased expression and activity of ACP could improve the absorption and utilization efficiency of P [ 41 ]. Our study showed that A74 had higher P accumulation, P uptake efficiency, and ACP activity under both LP and LPS stress than A6 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In response to P deficiency, plants evolved a series of intelligent adaptive mechanisms to improve P availability and increase its uptake efficiency, one of which was the production and secretion of acid phosphatase (ACP) [ 39 , 40 ]. The increased expression and activity of ACP could improve the absorption and utilization efficiency of P [ 41 ]. Our study showed that A74 had higher P accumulation, P uptake efficiency, and ACP activity under both LP and LPS stress than A6 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown if such a Pi negative feedback mechanism controls PHOSPHO1 expression, but the increased osteoclast resorption observed in ROD will bring about the release of Pi which will contribute to the observed hyperphosphatemia and impede the skeleton from exerting its normal reservoir function when serum Pi concentrations increase ( Hruska et al 2008 ). In such a scenario, the resulting Pi stress conditions experienced by the skeleton may drive higher PHOSPHO1 expression in a similar way to the LePS2 protein and other phosphatases such as OsACP1 a PHOSPHO1-like acid phosphatase in rice ( Deng et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PAP10 (that shows both SAP and IAP properties) in Arabidopsis and rice have been found to significantly increase the plant’s ability to degrade Po and tolerance to low Pi stress ( Wang et al., 2011 ; Deng et al., 2020 ). PNP and AT5G51260 regulate Pi tolerance by releasing Pi during polynucleotide synthesis from nucleotide diphosphates or triphosphates ( Marchive et al., 2010 ; Deng et al., 2021 ). We also predicted several genes with roles in phytohormone and sugar signalling pathways and root modulation.…”
Section: Discussionmentioning
confidence: 99%